Comparative study on combustion and thermodynamics performance of gasoline direct injection (GDI) engine under cold start and warm-up NEDC. (1st February 2019) - Liu, Qi; Liu, Jingping; Fu, Jianqin; Li, Yangyang; Luo, Baojun; Zhan, Zhangsong; Deng, Banglin
Highlights: Chassis dynamometer tests for gasoline-powered vehicle were carried out under cold start and warm up NEDC. The combustion rate of ICE in each stage under cold start and warmed up NEDC was compared. The thermodynamics process of ICE under NEDC were disintegrated and then quantitatively analyzed. Only in early stage ICE performance between cold start and warmed up NEDC differs obviously. The EEE in the early stage of cold start NEDC decreases largely due to the lower EER. Abstract: In this study, the chassis dynamometer tests for a gasoline-powered passenger vehicle were carried out under cold start and warm-up NEDC. The operating states, combustion and performance parameters of engine were measured continuously during vehicle driving cycles. Then, the combustion and thermodynamics processes under cold start and warm-up NEDC were compared and the influence factors for their differences were revealed. Results show that, since valve timing of tested engine is almost the same under cold start and warm-up conditions, it is not the main influence factor for the differences of in-cylinder RGF and EER. Although in-cylinder RGF decreases during cold start NEDC, the gap is too small to make any difference. Only in the early stage of NEDC, cold start has an obvious influence on in-cylinder combustion and thermodynamics processes of engine. For example, sparking timing is retarded, and SOC as well as 50% combustion position is further retarded. However, the heat transfer loss is also reduced due to the lower combustion temperature, thus the influence of later sparking timing on the indicated thermal efficiency of engine is restricted to some extent under cold start condition. All these provide theoretical guidance for improving engine actual performance.